Formation of Al3Ni2-type nanocrystalline 3 phases in the Al-Cu-Ni system by mechanical alloying - Yadav T.P.; Mukhopadhyay N.K.; Tiwari R.S.; Srivastava O.N. (My University, 2025)
An elemental powder mixture of Al (70 at.%), Ni (15 at.%) and Cu (15 at.%) was milled in a high-energy ball mill for various times ranging from 10 to 100 h to form ternary intermetallic alloys. X-ray diffraction and transmission electron microscopy techniques were employed for characterization of the samples. The dissolution of the individual elements into an alloy led to the formation of a 3 vacancy-ordered phase after 100 h of milling. This phase was found to be quite stable against milling, and no other crystalline and amorphous phases could be detected. The powder after 100 h of milling was found to contain mostly 3 nanophases with partial ordering, and with crystallite sizes in the range 10-20 nm along with a lattice strain of 0.675%. The milled powder, after annealing at 700C for 20, 40 and 60 h, revealed the formation of a strain-free and ordered 3 phase with a crystallite size of 80 nm, indicating grain coarsening. It is interesting to note that the mechanical energy imparted during milling could not completely destroy the vacancy ordering in the 3 phase, unlike other stoichiometric Al-Cu-transition metal (TM) systems, where the disordered B2 (bcc) phase is commonly observed instead of any vacancy-ordered phases.